Humiliation, pride and identity in the digital age: unpacking Chinese online nationalism - Cheng, Jing (2018)
Nationalism has been an important issue for China in both domestic politics and international relations. In the Post-Tiananmen Era, the Chinese Communist Party (CCP) turned to nationalism as an ideological instrument to bolster the faith of the Chinese people and legitimise the Party’s rule. Meanwhile, the early 1990s also witnessed rapid developments in information and communications technologies (ICTs) in China, which have catalysed the emergence of online nationalism. Much of the existing literature focuses on either the external impact of Chinese nationalism on foreign policy or highlights the rise of popular nationalism as an independent force that makes the state fragile. There is, however, insufficient attention paid to the internal construct of Chinese nationalism. In the digital age, it also becomes increasingly evident that contemporary Chinese nationalism cannot be properly understood without reference to the role of digital communication.